Two sisters : a father, his daughters, and their journey into the Syrian jihad - Seierstad, Åsne, 1970- (Farrar, Straus and Giroux, 2018)
The riveting story of two sisters' journey to the Islamic State and the father who tries to bring them home. Asne Seierstad puts the problem of radicalization into painfully human terms, using instant messages and other primary sources to reconstruct a family's crisis from the inside. Eventually, she takes us into the hellscape of the Syrian civil war, as Sadiq risks his life in pursuit of his daughters, refusing to let them disappear into the maelstrom. This is a relentless thriller and a feat of reporting with profound lessons about belief, extremism, and the meaning of devotion.